Involvement of Glucagon in Preventive Effect of Menthol Against High Fat Diet Induced Obesity in Mice - Khare, Pragyanshu; Mangal, Priyanka; Baboota, Ritesh K.; Jagtap, Sneha; Kumar, Vijay; Singh, Dhirendra Pratap; Boparai, Ravneet K.; Sharma, Shyam S.; Khardori, Romesh; Bhadada, Sanjay K.; Kondepudi, Kanthi K.; Chopra, Kanwaljit; et al. (Frontiers in Pharmacology, 2018)
Glucagon mediated mechanisms have been shown to play clinically significant role in energy expenditure. The present study was designed to understand whether pharmacological mimicking of cold using menthol (TRPM8 modulator) can induce glucagon-mediated energy expenditure to prevent weight gain and related complications. Acute oral and topical administration of TRPM8 agonists (menthol and icilin) increased serum glucagon concentration which was prevented by pre-treatment with AMTB, a TRPM8 blocker. Chronic administration of menthol (50 and 100 mg/kg/day for 12 weeks) to HFD fed animals prevented weight gain, insulin resistance, adipose tissue hypertrophy and triacylglycerol deposition in liver. These effects were not restricted to oral administration, but also observed upon the topical application of menthol (10% w/v). The metabolic alterations caused by menthol in liver and adipose tissue mirrored the known effects of glucagon, such as increased glycogenolysis and gluconeogenesis in the liver, and enhanced thermogenic activity of white and brown adipose tissue. Pearson correlation analysis suggests a strong correlation between glucagon dependent changes and energy expenditure markers. Interestingly, in-vitro treatment of the serum of menthol treated mice increased energy expenditure markers in mature 3T3L1 adipocytes, which was prevented in the presence of non-competitive glucagon receptor antagonist, L-168,049, indicating that menthol-induced increase in serum glucagon is responsible for increase in energy expenditure phenotype. In conclusion, the present work provides evidence that glucagon plays an important role in the preventive effect of menthol against HFD-induced weight gain and related complications.